Penguatan Pendidikan Karakter Nasionalis Siswa Sekolah Dasar Melalui Pembiasaan Sabtu Bersih dan Sehat - Nur Fitriyah, Erika; Supriyadi, Supriyadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Instilling character education is expected to be very helpful in forming role models to become individuals with noble character. Character education from an early age is the first step in building children's character, so education from an early age is needed. With a strong moral foundation and positive character, a person repeatedly thinks about doing those negative things. Because it is at this age that children have a golden period for personality development, namely the age of kindergarten and elementary school. Children's concern for the environment is not only the responsibility of the teacher but also parents at home to always remind and provide support to children to continue to apply environmental care as taught at school, in this way it will make children more aware of the cleanliness of the environment around them. Therefore, developing the character of caring for the environment in children from an early age is very important, if children are not taught about keeping the environment clean from a young age, then later into adulthood, children will not understand how to live in their own environment. Because as social beings we should live together with other people, therefore character needs to be nurtured from childhood so that children can live well in their environment later. Keywords: Character Education; Hygiene; Elementary School Children.